A National Analysis of Long-term Survival Following Thoracoscopic Versus Open Lobectomy for Stage I Non-small-cell Lung Cancer. Issue 1 (January 2019) - Yang, Chi-Fu Jeffrey; Kumar, Arvind; Klapper, Jacob A.; Hartwig, Matthew G.; Tong, Betty C.; Harpole, David H.; Berry, Mark F.; D'Amico, Thomas A.
Abstract : Objective: The objective of this study was to compare the long-term survival of open versus thoracoscopic (VATS) lobectomy for early stage non-small-cell lung cancer (NSCLC). Background: Data from national studies on long-term survival for VATS versus open lobectomy are limited. Methods: Outcomes of patients who underwent open versus VATS lobectomy for clinical T1–2, N0, M0 NSCLC in the National Cancer Data Base were evaluated using propensity score matching. Results: The median follow-up of 7114 lobectomies (5566 open and 1548 VATS) was 52.0 months. The VATS approach was associated with a better 5-year survival when compared to the open approach (66.0% vs. 62.5%, P = 0.026). Propensity score matching resulted in 1464 open and 1464 VATS patients who were well matched by 14 common prognostic covariates including tumor size and comorbidities. After propensity score matching, the VATS approach was associated with a shorter median length of stay (5 vs. 6 days, P < 0.001). The VATS approach was not significantly different compared with the open approach with regard to nodal upstaging (11.6% vs 12.3%, P = 0.53), 30-day mortality (1.7% vs 2.3%, P = 0.50) and 5-year survival (66.3% vs 65.8%, P = 0.92). Conclusions: In this national analysis, VATS lobectomy was used in the minority of patients with stage I NSCLC. VATS lobectomy was associated with shorter length of stay and noninferior long-term survival when compared with open lobectomy. These results support previous findings from smaller single- and multi-institutional studies that suggest that VATS does not compromise oncologic outcomes when used for early-stage lung cancer and suggest the need for broader implementation of VATS techniques. Abstract : Supplemental Digital Content is available in the text